Designing a competency system model with emphasis on employee dignity using the grounded theory approach - Shahrokhi sardoo , Fatemeh; Sayadi, Saeed; Nikpour , Amin; Madahian , Shiva; Molaei , Hamidreza (Social Determinants of Health, 2025)
Background: In today’s complex and competitive organizational environments, designing competency systems that enhance performance while upholding employee dignity has become a strategic priority in HR management. Employee dignity, defined as the recognition of individual worth, respect, and fair treatment in the workplace, is a multidimensional concept influencing motivation and organizational commitment. This study, using the grounded theory approach, aimed to develop a competency system model that integrates and promotes the principles of employee dignity within organizational practices. Methods: This research employed a mixed-methods design (qualitative–quantitative). In the qualitative phase, grounded theory (Strauss and Corbin approach) was used to analyse data from semi-structured interviews with 18 HR managers and experts. In the quantitative phase, the proposed model was tested using structural equation modelling (SEM) on a sample of 260 employees, and further validated through a nonlinear Bayesian model. Model fit was assessed using indices such as RMSEA, CFI, and TLI. Integration of qualitative and quantitative findings was performed through a comparative analysis, ensuring theoretical saturation aligned with empirical validation. Results: The qualitative results led to the identification of seven causal categories within the competency system, including professional, cognitive, and organizational competencies. In the quantitative prioritization, professional, cognitive, and organizational competencies received the highest weights. Path analysis revealed that these competencies significantly impacted job dignity and, subsequently, organizational performance. Model fit indices confirmed the high predictive power and accuracy of the conceptual model. Conclusion: The developed model presents a comprehensive and localized framework for a competency system that can serve as a foundation for human resource policies aimed at enhancing employee dignity and productivity.